PRODUCT DIVERSIFICATION AND E-COMMERCE MARKETING IN AN EFFORT TO INCREASE SALES (USAHA ALFIRA HENNA ART BUSINESS) - ALFIRA; MUHAMMAD JUFRI, SUMIATI TAHIR, ASMAYANTI, ANDIKA ISMA (CV. Adiba Aisha Amira, 2025)
With the advancement of time and internet technology, business actors are encouraged to adapt and seize existing opportunities, one of which is the utilization of Shopee's e-commerce with attractive features that can support a wider market share. Additionally, to meet consumer desires, a business needs to innovate through product development, one of which is product diversification, a business development strategy to expand product reach, prepare new markets, and reduce business risks. This research aims to examine Product Diversification and E-Commerce Marketing in Efforts to Increase Sales of Alfira Henna Art Business. The research method used is qualitative descriptive with a focus on the study of Concentric Diversification and E-Commerce Marketing Features of Shopee. The analysis stages include market trend research, new product development, and product trials with 3 Henna Artist informants to obtain responses regarding the launched products in terms of product quality, product durability, suggestions, and feedback from informants, resulting in the final product development with the addition of products on Shopee e-commerce. The research results show that the new Henna product development through concentric diversification, Amora White Henna and Amora Nude Henna products, aligns with consumer desires, receives positive responses regarding quality differentiation from competitors, and utilizes Shopee e-commerce marketing features used by Alfira Henna Art Business such as Store Promotions, Discount Packages, Follow Store Vouchers, Discount Packages, and Shopee Ads. This also expands the market reach and increases the sales reach of Alfira Henna Art Business compared to before. Thus, it can be concluded that Product Diversification through concentric diversification, namely Amora White Henna and Amora Nude Henna, aligns with consumer needs, and the E-Commerce Marketing Features of Shopee have proven effective in reaching a broader market share and driving the growth of Alfira Henna Art business.